Effects of 1-MCP on the post-harvest quality of the orange cv. Pera stored under refrigeration - Rosa, Cassia Inês; Clemente, Edmar; Oliveira, Dalany; Todisco, Katieli; Costa, Jose Maria (Revista Ciência Agronômica, 2016)
The aim of this work was to analyse the effects of 1-MCP upon the post-harvest quality of the orange cv. Pera stored for 45 days at a temperature of 7 ºC. The fruit was divided into four treatments, and then submitted to the application of three concentrations of 1-methylciclopropene (0.1, 0.5 and 1.0µL.L-1) for a period of 12 hours.The fruitwas again then stored at a temperature of 7 ºC. The rate of respiration was determined, together withcoloration of the epidermis, SS, TA, ratio, vitamin C, total carotenoids, phenolic compounds, total and reducing sugars, weight loss and juice yield. The data were submitted to analysis of variance (F-Test), and the averages were analysed by regression (P≤0.05). According to the results, it could be seen that higher doses of 1-MCP may have caused chemical stress to the orangesunder evaluation, being responsible for the increasein the rate of respiration.Achange in coloration of the epidermis from green to yellow/orange was delayed by the application of 1-MCP; the application of 1-MCP did not cause any alteration to such chemical characteristics as SS, TA, ratio, carotenoids, phenolic compounds or sugars.